Concealed Weapons on Campus : Do They Make People Feel Safer? - Siedlitz, Brady; Mort, Angelina; Alger, Haley; Hsieh, Ming-Li (My University, 2018)
The current study primarily seeks to understand how perceptions of campus safety are related to physical institutional features, potential victimization, fear of crime, and attitudes toward concealed handguns on campus.
Color poster with text, pie charts, tables, and graphs.
Keywords: Posters; Firearms; Campus violence; Firearms - Safety measures - Study and teaching; Violence